2016
DOI: 10.1016/j.kint.2015.11.017
|View full text |Cite
|
Sign up to set email alerts
|

Uroplakin 1b is critical in urinary tract development and urothelial differentiation and homeostasis

Abstract: Proper development and maintenance of urothelium is critical to its function. Uroplakins are expressed in developing and mature urothelium where they establish plaques associated with the permeability barrier. Their precise functional role in development and disease is unknown. Here, we disrupted Upk1b in vivo where its loss resulted in urothelial plaque disruption in the bladder and kidney. Upk1bRFP/RFP bladder urothelium appeared dysplastic with expansion of the progenitor cell markers, Krt14 and Krt5, incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 38 publications
(47 reference statements)
1
24
1
Order By: Relevance
“…Loss of Upk1b expression in Upk1b RFP/RFP mice is predicted to block Upk1b/3a heterodimer production completely abrogating apical plaque/AUM formation. Our studies confirmed that Upk1b RFP/RFP mice lack Upk1b expression and do not develop apical plaques/AUMs throughout their urinary tract [12]. Interestingly, even though Upk1b is more widely expressed than its other family members (see below), we did not observe any other gross morphological or functional deficits in Upk1b RFP/RFP mice besides those associated with the urinary tract.…”
Section: Upk1brfp/rfp Ablation Mice and Urothelial Dysmorphogenesissupporting
confidence: 84%
See 4 more Smart Citations
“…Loss of Upk1b expression in Upk1b RFP/RFP mice is predicted to block Upk1b/3a heterodimer production completely abrogating apical plaque/AUM formation. Our studies confirmed that Upk1b RFP/RFP mice lack Upk1b expression and do not develop apical plaques/AUMs throughout their urinary tract [12]. Interestingly, even though Upk1b is more widely expressed than its other family members (see below), we did not observe any other gross morphological or functional deficits in Upk1b RFP/RFP mice besides those associated with the urinary tract.…”
Section: Upk1brfp/rfp Ablation Mice and Urothelial Dysmorphogenesissupporting
confidence: 84%
“…Superficial umbrella cells elaborating a rigid apical plaque that plays a key role in modulating membrane permeability, integrity, homeostasis and host response to pathogens [710]. Apical plaques are principally composed of Upk protein particles arranged into 2D crystals (Figure 2) [12]. Upk proteins are highly conserved among mammals and to date five Upk proteins have been identified as constituents of apical plaques [13, 14].…”
Section: Upks and Apical Plaquesmentioning
confidence: 99%
See 3 more Smart Citations